Effective Trapping Reduction in SiO2/GaN MOS Structure by High Pressure Water Vapor Annealing. (1st January 2019) - Lin, Tengda; Uenuma, Mutsunori; Fururkawa, Masaaki; Bermundo, Juan Paolo Soria; Ishikawan, Yasuaki; Uraoka, Yukiharu
Abstract : Constant current biased voltage versus injection electron fluence (V-F) and High-Low frequency C-V measurements were conducted for GaN-SiO2  system treated by high pressure water vapor annealing (HPWVA). Combined with a kinetic rate analysis based on electron trapping and trap generation, a smaller amount of interface traps as well as a less severe trapping behavior is confirmed. As a result, HPWVA can be a promising method for improving both bulk and interface qualities of GaN/SiO2  MOS structure, which plays an important role in power electronics.